Research on Service Performance of Buton Rock Asphalt and Rubber Powder Composite Modified Asphalt Pavement - Yang Qiao (Forest Chemicals Review, 1970)
The performance of road surface has received more attention due to the increase of vehicle axle load caused by the growth of national economy. The polymer-modified asphalt represented by SBS is limited in use due to its high preparation cost, complex modification process, and weak low-temperature performance. Therefore, new modified asphalt materials are the key research directions of scholars from all over the world. In this paper, the matrix asphalt was modified with different dosage combinations of Buton rock asphalt and rubber powder, in order to obtain the composite modified asphalt with higher high and low temperature performance than SBS. From a theoretical point of view, it is feasible to demonstrate that the pavement performance of Buton rock asphalt and rubber powder composite modified asphalt is greatly improved compared with matrix asphalt; The content of Buton rock asphalt and rubber powder has different degrees of influence. The optimal combination of various factors is selected as 20% BRA+22% rubber powder. It provides a basis for further research on the road performance of the asphalt mixture, and provides a reference for further research on composite modified asphalt.